IDENTIFIKASI TUMBUHAN PENGHASIL BAHAN MAKANAN DI LINGKUNGAN MASYARAKAT ADAT KENEGERIAN RUMBIO UNTUK PENGEMBANGAN MODUL PEMBELAJARAN PADA KONSEP KLASIFIKASI TUMBUHAN KELAS X SMA - Nursal "; Yuslim Fauziah; M. Faisal Rizqi (Biogenesis, 2017)
ABSTRACT The Researchers have done to collect the data, kind of plants as produce foodstuff and the benefit in society of Rumbio on July-August 2015. Result of research was developing module learning on plant classification concept at senior high school X. This research had two phases. The first phase was collecting the data of plant as produce foodstuffspecies with survey method (interview and observation). Parameter in this research was kind of plants as produce foodstuff in Rumbio tradition society and benefits. The Data analysis used descriptive method. The second phase, develop of module learning from result of research in first phase and used ADDIE model (Analyze, Design, Development, Implementation, and Evaluation)in 3 phase; analyze, design, development. Result of this research found 75 species and 37 plants of it plants are produce foodstuff in Rumbio Tradition society. Part of plants 36 species was fruit, plants as produce foodstuff in yard on 62% and unworked 38% plants species. The average of result in module learning was Valid on 3,99. So, this module learning may to try in Biologic in Senior High School X. Keyword: Plants as Produce Foodstuff, Rumbio Tradition Society, Module Learning